BO‘LAJAK TEXNOLOGIK TA’LIMI YO’NALISHI O‘QITUVCHILARNI XALQ HUNARMANDCHILIGI A‘MALIY DARSIDA KA‘SBIY KOMPONENTLIGINI O‘RGATISHNING MUAMMO VA YECHIMLARI - Qutlimuradov, K.A. (SCIENCE and SOCIETY, 2022)
The article discusses the formation of professional competence in the training of teachers, the formation of professional competence, the creation of pedagogical and psychological conditions for the professional and personal development of future teachers, modernization on the basis of a competency approach, the features of professional competence. In terms of the requirements for the level of professional training, competence refers to the ability of students to use a set of knowledge, skills and methods of activity in a specific situation.
Keywords: modern education and upbringing; national spirituality; didactic views; goal; interdisciplinary communication